2021
DOI: 10.1002/jmv.26770
|View full text |Cite
|
Sign up to set email alerts
|

Performance and feasibility of universal PCR admission screening for SARS‐CoV‐2 in a German tertiary care hospital

Abstract: Anamnestic screening of symptoms and contact history is applied to identify coronavirus disease 2019 (COVID-19) patients on admission. However, asymptomatic and presymptomatic patients remain undetected although the viral load may be high. In this retrospective cohort study, all hospitalized patients who received polymerase chain reaction (PCR) admission testing from March 26th until May 24th, 2020 were included. Data on COVID-19-specific symptoms and contact history to COVID-19 cases were retrospectively extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 41 publications
(67 reference statements)
3
41
0
1
Order By: Relevance
“…For more than a year, the COVID-19 pandemic has been a worldwide public health challenge. As well as contact tracing, contact reduction, quarantine, and vaccination, the early testing and detection of infectious persons is key in mitigating the spread of disease [1] .…”
Section: Introductionmentioning
confidence: 99%
“…For more than a year, the COVID-19 pandemic has been a worldwide public health challenge. As well as contact tracing, contact reduction, quarantine, and vaccination, the early testing and detection of infectious persons is key in mitigating the spread of disease [1] .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 0.07% of the asymptomatic patients and attendants tested positive for SARS-CoV-2 RNA by PCR before the scheduled admission. Regarding universal SARS-CoV-2 PCR screening before admission, Krüger et al [1] reported that 27 of 6,940 patients (0.4%) were positive at a tertiary care hospital in Germany, and Scheier et al [2] demonstrated similar results at four hospitals in Zurich (8 of 2,278 positive patients, 0.4%). These studies were conducted in areas where the COVID-19 prevalence was higher than in Tokyo.…”
Section: Discussionmentioning
confidence: 99%
“…Universal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) polymerase chain reaction (PCR) screening before admission has been adopted in several hospitals to prevent nosocomial SARS-CoV-2 transmission from asymptomatic and pre-symptomatic patients. However, the usefulness of this type of screening remains unclear as it depends on the regional COVID-19 prevalence, and, to date, only a few large-scale studies have been conducted [1] , [2] , [3] . Here, we report the universal COVID-19 PCR screening results for over 12,000 asymptomatic patients and their attendants before admission to a hospital in Tokyo, Japan, to evaluate the universal screening benefits.…”
Section: Introductionmentioning
confidence: 99%
“…However, antibody testing is useful in determining exposure to SARS-CoV-2, especially in patients with potential post-COVID-19-symptoms, as well as for epidemiological investigations. In patients with low viral RNA load detected by PCR, antibody testing helps to distinguish between the beginning of a SARS-CoV-2 infection, when no antibodies are detectable and infectivity is expected to increase, and the persistent PCR positivity after an undiagnosed SARS-CoV-2 infection, when antibodies should be detectable and no further infectivity is expected (6). Antibody testing also allows the identification of suitable convalescent plasma donors and may become important for the determination of post-vaccination immunity.…”
Section: Introductionmentioning
confidence: 99%